2022
DOI: 10.7554/elife.66704
|View full text |Cite|
|
Sign up to set email alerts
|

Global analysis of cell behavior and protein dynamics reveals region-specific roles for Shroom3 and N-cadherin during neural tube closure

Abstract: Failures of neural tube closure are common and serious birth defects, yet we have a poor understanding of the interaction of genetics and cell biology during neural tube closure. Additionally, mutations that cause neural tube defects (NTDs) tend to affect anterior or posterior regions of the neural tube but rarely both, indicating a regional specificity to NTD genetics. To better understand the regional specificity of cell behaviors during neural tube closure, we analyzed the dynamic localization of actin and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 77 publications
5
17
1
2
Order By: Relevance
“…High-resolution imaging of NP morphogenesis revealed that the anterior and posterior regions of the NP display distinct morphogenetic behaviour. This is an agreement with a recent study that also detected distinct patterns of behaviour at the posterior and anterior NP (Baldwin et al, 2022). Specifically, here we show that whereas the NP narrows and elongates, the anterior part of the tissue displays a polarized anterior movement.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…High-resolution imaging of NP morphogenesis revealed that the anterior and posterior regions of the NP display distinct morphogenetic behaviour. This is an agreement with a recent study that also detected distinct patterns of behaviour at the posterior and anterior NP (Baldwin et al, 2022). Specifically, here we show that whereas the NP narrows and elongates, the anterior part of the tissue displays a polarized anterior movement.…”
Section: Discussionsupporting
confidence: 94%
“…S6B,C). In agreement with our data, Crispr/Casmediated knock out of Shroom3 in Xenopus embryos leads to a mild effect on the polarity of T1 transitions, but does not affect the number of T1 transitions and CE-mediated tissue deformation (Baldwin et al, 2022). Altogether, our data show that NTC is clearly biphasic with an early CE-driven phase that is spatially restricted to the posterior NP, followed by a second phase driven by generalized AC across the entire NP (Fig.…”
Section: Spatiotemporal Contribution Of Ap During Ntcsupporting
confidence: 92%
“…The transformation of the flat neuroepithelium to the neural tube is primarily driven by forces generated by intrinsic morphogenetic events. Convergent extension and apical constriction are the two main morphogenetic movements taking place within the neuroepithelium during neural tube closure ( Keller et al, 1992 ; Davidson and Keller, 1999 ; Hildebrand and Soriano, 1999 ; Haigo et al, 2003 ; Nishimura et al, 2012 ; Zanardelli et al, 2013 ; Christodoulou and Skourides, 2015 ; Baldwin et al, 2022 ). In addition to neural plate generated forces, it has been suggested that extrinsic forces stemming from the adjacent surface ectoderm and the underlying somitic mesoderm actively contribute to neural tube closure ( Schroeder, 1970 ; Karfunkel, 1974 ; Jacobson and Gordon, 1976 ; Moury and Schoenwolf, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, formin homology domain-containing (Fhod)3 is selectively expressed in apically convex regions of the anterior neuroepithelium overlying the rhombomeres and its deletion prevents apical constriction, causing exencephaly in mice (Sulistomo et al, 2019). In Xenopus , simultaneous accumulation of F-actin and N-cadherin (CDH2) parallels apical constriction anteriorly, whereas N-cadherin does not increase in the constricting posterior neuroepithelium (Baldwin et al, 2022). Important differences between Xenopus and amniotes include the lack of a pseudostratified neuroepithelium and brevity of neural tube closure relative to cell cycle progression in the former (Nikolopoulou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both apicomedial and cell junction actomyosin can contribute to apical shrinkage. In the stratified neuroepithelium of Xenopus , apicomedial F-actin accumulation is associated with apical shrinkage in the presumptive brain, whereas both apicomedial and cortical accumulation can correlate with apical shrinkage in the spinal region (Baldwin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%